Mapping Research on Environmental Awareness: A Systematic Literature Review (2000–2025) - Dewiyanti Fadly; Dedy Setyawan (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Environmental awareness has emerged as a strategic response to the triple planetary crisis of climate change, pollution, and biodiversity loss. Despite the rapid growth of related research, studies remain fragmented across disciplines, creating inconsistencies in concepts and measurement. This study aims to map research trends, effective teaching approaches, and key variables associated with environmental awareness in education through a bibliometric-based systematic literature review of Scopus-indexed publications from 2000–2025. Using PRISMA procedures and VOSviewer analysis, 43 selected articles were examined to identify publication patterns, keyword networks, and dominant research themes. The findings reveal a significant increase in publications, particularly after 2023, indicating growing global attention to environmental awareness as a priority research topic. Social sciences dominate the field, yet the literature shows strong interdisciplinary expansion involving environmental science, technology, energy, and health. Effective interventions include sustainability-based environmental education, learner-centered and participatory learning, knowledge–attitude–behavior frameworks, and technology-enhanced strategies such as gamification. Key associated variables include educational context, sustainability, environmental knowledge, attitudes, and pro-environmental behavior. Overall, environmental awareness is positioned as a multidimensional educational construct that bridges knowledge and attitudes with responsible environmental action, highlighting the importance of curriculum integration and future longitudinal research.